A potential future Fontan modification: preliminary in vitro data of a pressure-generating tube from engineered heart tissue. (26th February 2022) - Köhne, Maria; Behrens, Charlotta Sophie; Stüdemann, Tim; Bibra, Constantin von; Querdel, Eva; Shibamiya, Aya; Geertz, Birgit; Olfe, Jakob; Hüners, Ida; Jockenhövel, Stefan; Hübler, Michael; Eschenhagen, Thomas; et al.
Abstract: OBJECTIVES: Univentricular malformations are severe cardiac lesions with limited therapeutic options and a poor long-term outcome. The staged surgical palliation (Fontan principle) results in a circulation in which venous return is conducted to the pulmonary arteries via passive laminar flow. We aimed to generate a contractile subpulmonary neo-ventricle from engineered heart tissue (EHT) to drive pulmonary flow actively. METHODS: A three-dimensional tubular EHT (1.8-cm length, 6-mm inner diameter, ca. 1-mm wall thickness) was created by casting human-induced pluripotent stem cell-derived cardiomyocytes (0.9 ml, 18 mio/ml) embedded in a fibrin-based hydrogel around a silicone tube. EHTs were cultured under continuous, pulsatile flow through the silicone tube for 23 days. RESULTS: The constructs started to beat macroscopically at days 8–14 and remained stable in size and shape over the whole culture period. Tubular EHTs showed a coherent beating pattern after 23 days in culture, and isovolumetric pressure measurements demonstrated a coherent pulsatile wave formation with an average frequency of 77 ± 5 beats/min and an average pressure of 0.2 mmHg. Histological analysis revealed cardiomyocytes mainly localized along the inner and outer curvature of the tubular wall with mainly longitudinal alignment. Cell density in the center of the tubular wall was lower. CONCLUSIONS: A simple tube-shaped contractile EHT was generated from human-induced pluripotent stem cells and developed a synchronous beating pattern. Further steps need to focus on optimizing support materials, flow rates and geometry to obtain a construct that creates sufficient pressures to support a directed and pulsatile blood flow. Abstract : Besides primary heart transplantation, the Fontan principle in all its variations is the only surgical treatment option for patients with single-ventricle anatomy [1, 2].